IMPLEMENTATION OF DAYCARE PROGRAM AT INTERNATIONAL PRESCHOOL CIPTA CREATIVE BANGSA PALEMBANG - Astri, Astri (Jurnal Asy-Syukriyyah, 2025)
This study analyzes the implementation of the daycare program at the International Preschool Cipta Kreatif Bangsa (CKB) Palembang. Using a qualitative phenomenological approach, the study was conducted from April to October 2024 with data collection techniques in the form of non-participant observation, structured interviews, and documentation. The results of the study show that the daycare program at CKB Palembang has been structured with various educational activities such as Happy Song and Education Game, Fun Cooking, and Life Basic Skills. The main challenges faced are the limited number of daycare teachers (only one person) who handles 15-20 children aged 2-6 years, and the absence of a formal evaluation system for each child. Supporting factors include opportunities for child socialization, skill development, and convenience for working parents, while inhibiting factors include health risks and limited individual attention. This program has integrated Islamic educational values ​​into daily activities to develop children's independence, responsibility, and discipline